A Companion to the Queenship of Isabel la Católica
1 online resource
Keywords: The queenship of the first European Renaissance queen regnant never ceases to fascinate. Was she a saint or a bigoted zealot? A pious wife or the one wearing the pants? Was she ultimately responsible for genocide? A case has been made to canonize her. Does she deserve to be called Saint Isabel? As different groups from fascists to feminists continue to fight over Isabel as cultural capital, we ask which (if any) of these recyclings are legitimate or appropriate. Or has this figure taken on a life of her own? Contributors to this volume: Roger Boase, David A. Boruchoff, John Edwards, Emily Francomano, Edward Friedman, Cristina Guardiola-Griffiths, Michelle Hamilton, Elizabeth Teresa Howe, Hilaire Kallendorf, William D. Phillips, Jr., Nuria Silleras-Fernandez, Caroline Travalia, and Jessica Weiss.